Analisis Faktor-Faktor yang Mempengaruhi Minat Berwirausaha di Bidang Jasa Boga pada Siswa Kelas XI Jurusan Tata Boga SMK Negeri 6 Bungo - Aisy, Rihhadatul; novalia, ratih juwita; wicaksono, Yelvia (Program Studi Pendidikan Vokasi Seni Kuliner, 2025)
This study aims to determine: the factors that influence the interest in entrepreneurship in the field of Culinary Arts in Culinary Arts students of SMK Negeri 6 Bungo in terms of intrinsic factors, extrinsic factors, and the most dominant factors influencing the interest in entrepreneurship in the field of Culinary Arts in Culinary Arts students of SMK Negeri 6 Bungo. This research is descriptive research with a quantitative approach. The study was conducted from April 14th to 16th, 2025, at Vocational High School 6 Bungo. The population consisted of 103 Culinary Arts students at Vocational High School 6 Bungo, and 30 students were selected using purposive sampling. Data collection techniques used questionnaires and documentation. Validity testing used product moment correlation technique with a value > 0.361, while reliability testing used Alpha Cronbach technique with a reliability coefficient of 0.845. Data analysis used quantitative descriptive analysis. The results of the study show that: the factors that influence the interest in entrepreneurship in the field of Culinary Arts in Culinary Arts students of SMK Negeri 6 Bungo are reviewed from intrinsic factors in the sub-variable of the need for income, it has a high tendency, from the sub-variable of feelings of happiness, it has a low tendency, and the sub-variable of self-esteem has a high tendency, the factors that influence the interest in entrepreneurship in the field of Culinary Arts in Culinary Arts students of SMK Negeri 6 Bungo are reviewed from extrinsic factors in the sub-variable of opportunity, it has a moderate tendency, from the sub-variable of education, it has a moderate tendency, and the sub-variable of family environment has a moderate tendency, the most dominant factor influencing the interest in entrepreneurship in the field of Culinary Arts in Culinary Arts students of SMK Negeri 6 Bungo is the intrinsic factor. Keywords: Factors, Entrepreneurial Interest, Culinary Services.